Patient actions and reactions after receiving negative results from expanded carrier screening - Kraft, Stephanie A. (Clin Genet, 2018)
With the expansion of carrier screening to general preconception and prenatal patient populations, most patients will receive negative results, which we define as indicating <25% risk of having a child with a genetic condition. Because there is limited experience with expanded carrier screening, it is important to understand how receiving negative results affects patients, especially as providers, payers, and policymakers consider whether to offer it. In this mixed-methods study, we asked preconception patients enrolled in the NextGen study about their expectations and experiences receiving negative expanded carrier screening results. Participants completed surveys at study enrollment (n=110 women, 51 male partners), after receiving carrier results (n=100 women, 38 male partners), after receiving secondary findings (n=98 women, 36 male partners), and 6 months after receiving results (n=95 women, 28 male partners). We also interviewed a subset of participants 12–24 months after receiving results (n=24 women, 12 male partners). We found minimal negative emotional impact and privacy concerns, increased confidence in reproductive plans, and few changes to health behaviors, although some patients made health decisions based on misunderstandings of their results. These findings suggest that expanded carrier screening causes minimal psychosocial harms, but systems are needed to reduce the risk of misinterpreting results.